Food Stall Owners’ Strategies in Response to Rice Price Surges: a Grounded Theory Analysis - Pratiwi, Pratiwi; Humaira, Putri Syifa; Putri, Annisa Nurwanda; Heikal, Jerry (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The contemporary rice price surges are affected by several factors including natural, production-related, and even political factors. Food stall business owners affected by these surges need to make optimal decisions and strategies to ensure their business survival. This research aimed at identifying the strategies adopted by the affected food stall business owners. The study used a qualitative method with a Grounded Theory approach by conducting interviews with 6 respondents consisting of food stall owners in Jakarta. Based on the findings, 22 codes forming 5 categories were identified. This identification concluded 3 strategical themes: Price Adjustments, Substitution, and Omni-Channel totalling 24 points. The most common strategy applied by the participants is Price Adjustments as common as 21 points. This strategy is adopted to mitigate the impact of rising rice prices and maintain operations by focusing on price adjustments (13 points), portion sizes (5 points), and rice quality (3 points). Keywords: Food Stall Business Strategy, Grounded Theory, Rice Price Surges.